1983
DOI: 10.1111/j.1532-950x.1983.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Exuberant Granulation Tissue in the Horse Evaluation of Four Methods

Abstract: Four methods of treating granulating wounds on the dorsal aspect of the metacar‐pophalangeal and metatarsophalangeal joints of ponies were evaluated. The following treatments were used: Group 1—excision of the granulation tissue with no further treatment; Group 2—cryosurgery; Group 3—excision of the granulation tissue and pressure bandage; and Group 4—excision of the granulation tissue and immobilization of the limb with a plaster cast. The wounds in Group 1 healed fastest, without producing exuberant granulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 7 publications
1
37
1
1
Order By: Relevance
“…Second-intention healing of wounds in the distal portion of the limbs is more complicated in horses than in other domestic species as a result of several factors, including minimal blood supply to the distal portion of the limbs, minimal amounts of underlying soft tissues, hypoxia, inability to immobilize the area, lack of cutaneous musculature, and infection or chronic inflammation. [1][2][3][4] Other complications associated with second-intention healing in this location include indolent wounds, hypergranulating wounds, and formation of sarcoids. 5 Wounds heal by contraction and epithelialization.…”
mentioning
confidence: 99%
“…Second-intention healing of wounds in the distal portion of the limbs is more complicated in horses than in other domestic species as a result of several factors, including minimal blood supply to the distal portion of the limbs, minimal amounts of underlying soft tissues, hypoxia, inability to immobilize the area, lack of cutaneous musculature, and infection or chronic inflammation. [1][2][3][4] Other complications associated with second-intention healing in this location include indolent wounds, hypergranulating wounds, and formation of sarcoids. 5 Wounds heal by contraction and epithelialization.…”
mentioning
confidence: 99%
“…Several studies have reported differences in the amount of exuberant granulation tissue produced by horses and ponies 2,3 . There is also a difference in the quantity and rate of formation of exuberant granulation tissue produced between trunk and limb wounds 2,3 . In horses, wounds on the distal aspect of the limb produce more exuberant granulation tissue than trunk wounds.…”
mentioning
confidence: 99%
“…There have been countless topical preparations and medications that have been applied to DLWs over the millennia and even in recent times, but few have actually been scientifi cally shown to possess signifi cant clinical effi cacy. There have been numerous studies comparing treatments such as corticosteroids [4] , platelet rich plasma [5] , occlusive dressings [6] , and collagen gel [7] , growth factors [8] and immobilization [9] , but no treatment has been shown to have a statistically significant effect on the healing rate of full thickness excisional skin wounds. The goals of treating DLWs include minimizing exuberant granulation tissue and facilitating contraction and epithelialization.…”
Section: Introductionmentioning
confidence: 99%